1999
DOI: 10.1002/(sici)1521-3773(19990301)38:5<693::aid-anie693>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Ln2Al3Si2 (Ln=Ho, Er, Tm): New Silicides from Molten Aluminum—Determination of the Al/Si Distribution with Neutron Crystallography and Metamagnetic Transitions

Abstract: Highly metallic compounds with a quasi-one-dimensional structure, the new ternary compounds Ln Al Si (Ln=Ho, Er, Tm) are synthesized in molten aluminum from lanthanoid and silicon as reagents. Their structures show a formally [Al Si ] framework that contains infinite Al zigzag chains and Si-Si dimers and accommodates rows of Ln ions in parallel tunnels. The compounds exhibit metamagnetic transitions at high magnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 6 publications
0
28
0
3
Order By: Relevance
“…Crystals of various metal–aluminum silicides grow easily in an aluminum melt below 900 °C, and a large number of such silicides has been identified. These reactions proceed rapidly; examples are the series RE 2 Al 3 Si 2 ( RE =Ho, Er, Dy, Tm)214 as well as the quaternary aluminum silicide Sm 2 Ni(Ni x Si 1− x )Al 4 Si 6 . Crystals as long as 4 mm form readily in the aluminum flux.…”
Section: Liquid Aluminum As a Fluxmentioning
confidence: 99%
“…Crystals of various metal–aluminum silicides grow easily in an aluminum melt below 900 °C, and a large number of such silicides has been identified. These reactions proceed rapidly; examples are the series RE 2 Al 3 Si 2 ( RE =Ho, Er, Dy, Tm)214 as well as the quaternary aluminum silicide Sm 2 Ni(Ni x Si 1− x )Al 4 Si 6 . Crystals as long as 4 mm form readily in the aluminum flux.…”
Section: Liquid Aluminum As a Fluxmentioning
confidence: 99%
“…Diffraction data were collected at 120 K using the above-mentioned routines. The results agree very well with previous room temperature work on R 2 Al 3 Si 2 (R ¼ Tb, Dy) [21], and on R 2 Al 3 Si 2 (R ¼ Ho, Er, Tm) [22], and unambiguously confirmed that the latter are compounds with no stoichiometry breadth. The unit cell parameters at 120 K were slightly smaller than those at room temperature yielding volume expansion coefficients (b) …”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…3, inset), corresponding to the onset of antiferromagnetic order, an observation that was confirmed from the analysis of the magnetic susceptibility data (Fig. 4d) Reports on the crystal structures and some of the properties of these compounds exist [21,22]. These materials crystallize as long needle-shaped crystals and all magnetic measurements were performed with magnetic field parallel to the direction of the needle, which was assumed to be the b-axis.…”
Section: Gdal X Si 2àxmentioning
confidence: 99%
“…6), was auch bei den isotypen Siliciden sowie Tb 2 Al 3 Si 2 bzw. Dy 2 Al 3 Si 2 der Fall sein du È rfte und bei Ho 2 Al 3 Si 2 [5] bereits festgestellt worden ist.…”
unclassified